2017
DOI: 10.1007/s00380-017-1063-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of renal perfusion impairment in a rat model of acute renal congestion using contrast-enhanced ultrasonography

Abstract: Renal congestion is caused by elevated central venous pressure (CVP), and decreases glomerular filtration in patients with congestive heart failure. Since real-time contrast-enhanced ultrasonography (CEUS) using microbubble-based contrast agents can visualize the perfused microvascular bed, we sought to evaluate the impairment of renal perfusion during acute renal congestion with CEUS. In Wister rats, CEUS of kidney was performed with the direct monitoring of CVP and intra-renal pressure (IRP). When CVP was el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…These animal experiments showed that renal perfusion was impaired as the CVP and renal interstitial pressure increase. 15 Similar to the experimental results, the TTP in CHF patients before treatment was significantly prolonged in this study. In the cortex, the TTP was shortened due to the improvement in renal congestion after CHF treatment; this indicates that the perfusion rate of the renal parenchyma was decreased as a result of renal congestion.…”
Section: Renal Perfusion Impairment In Chf Patientssupporting
confidence: 88%
See 1 more Smart Citation
“…These animal experiments showed that renal perfusion was impaired as the CVP and renal interstitial pressure increase. 15 Similar to the experimental results, the TTP in CHF patients before treatment was significantly prolonged in this study. In the cortex, the TTP was shortened due to the improvement in renal congestion after CHF treatment; this indicates that the perfusion rate of the renal parenchyma was decreased as a result of renal congestion.…”
Section: Renal Perfusion Impairment In Chf Patientssupporting
confidence: 88%
“…36,37 In our previous animal experiments, perfusion impairment due to acute renal congestion was more pronounced in the medulla than in the cortex. 15 Therefore, in the assessment of renal congestion, evaluation of the medullary circulation may be more important than evaluation of the cortical circulation. In the present study, improved blood volume was observed in the cortical and medullary regions, and the perfusion rate of the cortex was restored after CHF treatment.…”
Section: Differences Between the Cortex And Medullamentioning
confidence: 99%
“…Recently, a rat model of acute renal congestion has been described by Komuro et al [86]. In this model, the femoral vein was cannulated with an indwelling catheter for the simultaneous monitoring of the CVP and injection of saline to create the acute renal congestion model.…”
Section: Saline Infusionmentioning
confidence: 99%
“…In this model, the femoral vein was cannulated with an indwelling catheter for the simultaneous monitoring of the CVP and injection of saline to create the acute renal congestion model. A bolus of saline is injected until the CVP increased to 10-15 mmHg [86]. However, being an acute model of renal congestion, the chronic phase cannot be investigated and systemic congestion was not induced.…”
Section: Saline Infusionmentioning
confidence: 99%
“…Previous studies have shown that a higher CVP impedes venous return [38,39] and worsens hepatic, renal, splanchnic, and cardiac microcirculatory flow and organ function [40][41][42]. Marik et al even reasons that CVP is the major determinant of organ capillary flow when the middle arterial pressure (MAP) is within an organ s autoregulatory range [40,43].…”
Section: Discussionmentioning
confidence: 99%